Pathogenesis of Drug Induced Non-Allergic Angioedema: A Review of Unusual Etiologies - Kalambay, Junior (Cureus, 2017)
Angioedema is the swelling of mucosal and sub-mucosal tissue. Typically, it manifests as the swelling of the face, lips, and tongue. Angioedema can be severe and life threatening when it involves the respiratory tract. Drug induced allergic angioedema and drug induced non-allergic angioedema differ in their mediator, their clinical presentations, and their management. In drug induced non-allergic angioedema, symptoms are resistant to antihistamine and corticosteroid treatment. The aim of the analysis was to identify which medications are associated with drug-induced non-allergic angioedema and to understand the mechanism of action via which of these medication cause angioedema.